2014
DOI: 10.1111/1471-0528.12500
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal interventions to reduce maternal distress: a systematic review and meta‐analysis of randomised trials

Abstract: Background Maternal distress can have adverse health outcomes for mothers and their children. Antenatal interventions may reduce maternal distress.Objective To assess the effectiveness of antenatal interventions for the reduction of maternal distress during pregnancy and for up to 1 year postpartum.Search strategy EBSCO, Medline, PubMed, Cochrane, secondary references of Cochrane reviews and review articles, and experts in the field.Selection criteria Randomised controlled trials in which the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 41 publications
1
58
0
10
Order By: Relevance
“…A systematic review of psychosocial and psychological preventive interventions reported a beneficial effect on the prevention of depressive symptomatology, especially in the short term (Dennis, 2013). In contrast, a meta-analysis, did not find that maternal distress was significantly reduced by preventive interventions (Fontein−Kuipers et al, 2014). Antenatal interventions have the potential to help not only the mother, but her infant in the longer term (Glover, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of psychosocial and psychological preventive interventions reported a beneficial effect on the prevention of depressive symptomatology, especially in the short term (Dennis, 2013). In contrast, a meta-analysis, did not find that maternal distress was significantly reduced by preventive interventions (Fontein−Kuipers et al, 2014). Antenatal interventions have the potential to help not only the mother, but her infant in the longer term (Glover, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatments are available for PND, but it is less clear whether strategies for preventive interventions in pregnancy are effective for both mothers (Dennis and Allen, 2008) and their infants and whether those interventions should be targeted towards women who are at greater risk of developing PND (Fontein−Kuipers et al, 2014). A systematic review of psychosocial and psychological preventive interventions reported a beneficial effect on the prevention of depressive symptomatology, especially in the short term (Dennis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in research into antenatal psychological techniques which aim to reduce anxiety and improve maternal satisfaction and perinatal mental health, and reduce pain, medical interventions and requests for caesarean sections (Fontein-Kuipers et al, 2014). These techniques include yoga, meditation, mindfulness, hypnosis, and psychoeducational therapies.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques include yoga, meditation, mindfulness, hypnosis, and psychoeducational therapies. A recent meta-analysis of such antenatal interventions showed a small but significant reduction in maternal distress in at-risk women (Fontein-Kuipers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Taking the limitations of the meta-analysis into account, the results showed that universal preventive strategies, for a general sample of healthy pregnant women, have no observed beneficial effect in reducing maternal distress (six trials, n = 2793, standardized mean difference, SMD -0.06; 95% confidence interval, 95% CI -0.14 to 0.01). However, a subgroup analysis of a selected sample of pregnant women with characteristics that made them more vulnerable to develop maternal distress showed a small but significant reduction of maternal distress as a result of preventive strategies (three trials, n = 1410; SMD -0.25; 95% CI -0.37 to -0.14).Interventions for the treatment of existing maternal distress also showed a small but significant reduction of maternal distress (three trials, n = 270; SMD -0.29, 95% CI -0.54 to -0.04) [33]. These results guided the focus of the intervention development towards selective and indicated prevention strategies.…”
mentioning
confidence: 98%